The conjunction between computer algebra and numerical methods - Aleksas Domarkas; Rimantas-Jonas Rakauskas; Silvijus Cicėnas (Lietuvos Matematikos Rinkinys)
The report presents the efficiency of using in common Maple and Matlab packages for finding solution (1), which describes the influence of n spherical particles to the external electrostatic field by means of general potential theory.